2020
DOI: 10.1002/iub.2408
|View full text |Cite
|
Sign up to set email alerts
|

LMNB2 is a prognostic biomarker and correlated with immune infiltrates in hepatocellular carcinoma

Abstract: BackgroundPrevious studies have suggested Lamin B2 (LMNB2) as an oncogene in lung cancer. However, the role of LMNB2 in hepatocellular carcinoma (HCC) remains unclear.MethodThe expression of LMNB2 was compared between HCC samples and non‐tumor samples in multiple datasets. In addition, the prognostic value of LMNB2 in HCC was also investigated. Furthermore, the cBioPortal was utilized to analyze the genomic alternation of LMNB2 in HCC. Besides, co‐expression genes and functional enrichment analysis were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In order to explore the relationship between immune-infiltration level and the two immune genes, we used CIBERSORT (Chen et al, 2018;Kong et al, 2020;Meng et al, 2021a) (https:// cibersort.stanford.edu/) to obtain the immune infiltration level of TCGA-KIRC data. The algorithm was run using LM22 signature and 1,000 permutations.…”
Section: Immune Infiltration Analysis Of Vav3 and Nr3c2mentioning
confidence: 99%
“…In order to explore the relationship between immune-infiltration level and the two immune genes, we used CIBERSORT (Chen et al, 2018;Kong et al, 2020;Meng et al, 2021a) (https:// cibersort.stanford.edu/) to obtain the immune infiltration level of TCGA-KIRC data. The algorithm was run using LM22 signature and 1,000 permutations.…”
Section: Immune Infiltration Analysis Of Vav3 and Nr3c2mentioning
confidence: 99%
“…In the future, whether LMNB2 regulated bladder cancer progression via regulating mitochondrial function will be studied. It has also been widely reported that LMNB2 affects the progression and metastasis of multiple types of cancers (15,16). LMNB2 was also aberrantly highly expressed in several cancer tissues, including liver and lung cancer (15,16).…”
Section: Discussionmentioning
confidence: 94%
“…Notably, LMNB2 is recognized as an oncogene affecting the progression of multiple types of cancers, such as ovarian, lung, and liver cancer (13)(14)(15). LMNB2 was revealed to be aberrantly highly expressed in tumor tissues, and correlated with the prognosis of several cancers, such as breast, liver, and lung cancer (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…There is no experimental evidence that LMNB2, BGN, and MFSD12 in this combination are associated with GA, and these are new PmBs identified in this study. LMNB2 belongs to the lamin family and is closely related to occurrence, development, and prognosis of liver cancer (Kong et al, 2020;Li X. N. et al, 2020). BGN is an important member of the leucinerich small proteoglycan family and an important component of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%